"Blessed are the poor": The Weberian spirit of capitalism under experimental scrutiny - Andrea Fazio; Tommaso Reggiani; Paolo Santori (Masaryk University, Faculty of Economics and Administration, 2024)
This paper empirically tests Max Weber's thesis on how religious narratives, particularly the Protestant Ethic, influence attitudes toward wealth redistribution. Weber suggested that the Protestant Reformation, led to the belief that economic success was a sign of divine favor, legitimizing wealth inequality. Using a variation of the dictator game with "blessed" framing, we measure how participants' redistribution behaviors change when primed with this narrative. Our results show that low-income Protestants exposed to the "blessed" narrative are less likely to redistribute wealth compared to Catholics, supporting Weber's idea that Protestants justify inequality through divine providence. Furthermore, a narrative analysis reveals that Protestants interpret "blessing" as divine election, while Catholics focus more on well-being. These findings suggest that religious narratives significantly shape economic behaviors and preferences for redistribution, providing empirical support for Weber's thesis.
Keywords: J14; J15; Z12; Z1; 330; dictator game; Max Weber; pro-social behaviour; redistribution